Design of telephone off-hook electronic switch - Mohamad Fadly, Ojek (Universiti Malaysia Sarawak (UNIMAS), 2002)
Nowadays, telephone plays an important role especially in the telecommunication field. This technology has growth increasingly towards the information technology era that is being achieved by our country. Telephone is one of the Telecommunication devices that can connect people throughout the world. World is said to become smaller with the existing technology. The changes of the telephone technology can be seen through the architecture design and application on it. Generally, this project is related with the use of the telephone set that is "automatic off-hook electronic switch" device, which cannot be found in other typical telephone. This device, when connected in parallel to a telephone line, one can take the telephone call automatically without lifting the handset and at the same time powers up any devices connected such as voice answering machine and tape recorder. For normal telephone, it is powered by the current drawing from the exchange office via the telephone line. One will have to lift switch hook by lifting the handset of the telephone (off-hook) to connect and put on back the handset (on-hook) to disconnect the phone call. It can be concluded that this project will help in the understanding of the telephone technology. It is hope that this new add-on application will give advantages to the user, besides preserving the telephone function itself.